The theory of vibrational wave movement in drying grain mixture - Bulgakov, Volodymyr; Булгаков, Владимир Михайлович; Булгаков, Володимир Михайлович; Nikolaenko, S.; Kiurchev, Serhii; Кюрчев, Сергій Володимирович; Кюрчев, Сергей Владимирович; Pascuzzi, S.; Arak, M.; Santoro, F.; Anifantis, A. S.; Olt, J. (My University, 2020)
This paper outlines a theory that involves the vibrational wave transportation of bulk grain during the course of passing that grain under an infrared radiation source, in a working thermal radiation drying chamber, and using a vibrational wave transporter belt that has been developed by the authors of this paper. The main outstanding feature of the proposed design is the presence of mechanical off-centre vibration drives which generate the vibration in the working rollers at a preset amplitude and frequency, thereby generating a mechanical wave on the surface of the flexible transporter belt which ensures the movement of bulk grain along the processing zone which itself is being subjected to infrared radiation. A calculation method was developed for the oscillation system that is used in conjunction with the vibrational transportation of the grain mass, in order to be able to determine the forces that may be present in the vibrational actuators, utilising for this purpose Type II Lagrange equations. The solving of the aforementioned integral equations on a PC yielded a number of graphical dependencies in terms of kinetic and dynamic parameters for the vibrational system described above; the analysis of those dependencies provided a rational structural, along with kinetic and dynamic indicators. According to the results that were taken from theoretical and experimental studies on the functioning of the developed infrared grain dryer combined with a vibrational exciter, stable movement for its working roller takes place if the angular velocity of a drive shaft is changed within the range of between 50 80 rads 1, whereas the amplitude of the indicated oscillations falls within the range of 3.0 4.0 mm. It has been discovered that a rational speed when transporting soy seeds during infrared drying falls between the range of between 0.15 0.60 cm s-1, whereas the amplitude of the indicated oscillations falls within the range of 3.0 4.0 mm. An increase of this parameter within the stated limits increases the time that it takes to achieve the stage in which a constant drying soy speed is reached by more than 2.5 times (from 205 seconds to 520 seconds), stabilising the figure at a level of 520 seconds, which makes it possible to recommend a range of transport speeds of between 0.15 0.40 cm s 1 under infrared radiation for the seeds in order to achieve the required moisture content with a single pass of the produce on the wave transporter. With that in mind, the power consumption levels for the vibrational exciter do not exceed 50W, whil 120 rads 1. The results of the experimental study that has been conducted indicated that a rational transportation speed for the soy seeds on the wave transporter under infrared radiation is between 0.15 0.40 cm s 1
Keywords: drying; grain; kinetic and dynamic parameters; model; quality; transportation